Description of a new blood-fluke, Cruoricola lates n. g., n. sp. (Digenea: Sanguinicolidae), from sea-bass Lates calcarifer (Bloch, 1790) (Centropomidae) - Herbert, Brett W.; Shaharom-Harrison, Faizah M.; Overstreet, Robin M. (Kluwer Academic Publishers, 1994)
A new blood-fluke, Cruoricola lates n. g., n. sp., is described from sea-bass Lates calcarifer cultured in Malaysia. It is also found in Thailand and Australia. All fish examined over 15 cm in length were infected in the type-locality. This sanguinicolid is differentiated from other genera by: the spherical seminal vesicle; the large, single testis extending beyond the intestinal caeca; the medial, bi-lobed ovary; and the single column of sub-marginal, laterally directed, evenly spaced spines. It has separate genital pores which are close together. Adults are found predominantly in the mesenteric venules of the venous circulation. Juveniles are commonest in the caudal kidney.